Large-scale tests of weld mesh versus high-tensile chain link mesh on mesh overlap load transfer - Brändle, R; Bucher, R (Ground Support 2023: 10th International Conference on Ground Support in Mining, 2023)
Rock damage and the risk of rockbursts are significant concerns in some underground excavations in mining and civil tunnels. The use of surface support, such as steel meshes, plays a crucial role in containing and securing failed or ejected rock, thus ensuring a safe working environment. This paper presents the findings of a test series conducted in Walenstadt, Switzerland. The primary objective was to assess the suitability of different ground support systems, consisting of various steel meshes and bolts, under dynamic loading conditions. The test setup allowed for the application of substantial amounts of energy on variable support systems, incorporating different bolt patterns and mesh types, in a large-scale manner. To analyse the behaviour of the systems, load cells, high-speed video analysis, and accelerometers were employed. The main focus of the experiments was on the total energy capacity of the different support arrangements, with particular attention given to the overlaps area of the various mesh types, which is considered one of the weak points in the support system. The results revealed that a combination of high tensile steel mesh with a specific bolt pattern exhibited a high energy capacity as surface support. The way impact loads were distributed during the stopping process depended on the strength and flexibility of the mesh, as well as the resistance and arrangement of the bolts. This paper provides valuable insights into the performance of various ground support systems under dynamic conditions. It emphasises the importance of adopting a comprehensive approach in the design of ground support systems. The results obtained from the large-scale testing and the analysis of state-of-the-art mesh types can contribute to the development of more effective and efficient surface support systems. Ultimately, this can enhance the safety and productivity of mining operations.
Keywords: ground support testing; mesh overlap; large-scale tests; chain link mesh